Bovine Herpesvirus-4-Based Vector Delivering Peste des Petits Ruminants Virus Hemagglutinin ORF Induces both Neutralizing Antibodies and Cytotoxic T Cell Responses - Macchi, Francesca (2018)
Peste des Petits Ruminants Virus (PPRV) is an extremely infective morbillivirus thatprimarily affects goats and sheep. In underdeveloped countries where livestock are themain economical resource, PPRV causes considerable economic losses. Protective liveattenuated vaccines are currently available but they induce antibody responses similar tothose produced in PPRV naturally infected animals. Effective vaccines able to distinguishbetween vaccinated and naturally infected animals are required to PPRV control anderadication programs. Hemagglutinin (H) is a highly immunogenic PPRV envelope glycoproteindisplaying both hemagglutinin and neuraminidase activities, playing a crucial rolein virus attachment and penetration. In this study, a recombinant Bovine Herpesvirus-4(BoHV-4)-based vector delivering an optimized PPRV-Hemagglutinin expression cassette,BoHV-4-A-PPRV-H-ΔTK, was assessed in immunocompetent C57BL/6 mice.BoHV-4-A-PPRV-H-ΔTK-immunization elicited both cellular and humoral immuneresponses with specific T cell, cytotoxic T lymphocyte, and sero-neutralizing antibodyagainst PPRV. These data suggest recombinant BoHV-4-A-PPRV-H-ΔTK as an effectivevaccine candidate to protect against PPRV herd infection and potentially applicable foreradication programs.